Comparative Distribution of Small Mammals Diversity in Protected and Non-Protected Area of Peninsular Malaysia - Julius, William-Dee; Faisal Ali, Anwarali Khan; Qhairil, Rosli; Muhd Amsyari, Morni; Isham, Azhar; Lee, Sim Lim; Roberta Chaya, Tawie Tingga; Mohd Ridwan, Abd Rahman (Penerbit Universiti Sains Malaysia, 2019)
Highlights ● An individual of Bandicota indica was recorded at Wang Kelian SP and is the first record for this site. This finding of this species in a primary forest shows the extension of its range. ● A single individual of Crocidura monticola and Suncus etruscus were caught at Ulu Gombak FR. The record of these two forest species indicates that Ulu Gombak FR, which is close to populated area, still holds quality habitat. The two shrew species were commonly found in forests with little or no disturbance. ● Listed as Vulnerable by IUCN Red List, Murina aenea was recorded at Sungkai WCC, highlighting the importance of the conservation centre as roosting site and eliminates the threat of habitat loss.